Ethics in Islam: Environmental Concern from the Perspective of the Hadith - Ridwan Hapani; Endad Musaddad (Aslim: Journal of Education and Islamic Studies, 2025)
The concept of ethics in islam related to responsibility for a clean environment, with a focus on the study of the hadiths of the Prophet Muhammad Saw. In Islamic teachings, cleanliness is not only seen as a physical aspect, but also part of spirituality and faith. The hadiths of the Prophet show that maintaining cleanliness is one of the real manifestations of faith, and that every individual has a responsibility to create a clean and healthy environment. This article reveals several important aspects, including: Cleanliness as part of faith, collective responsibility for environmental cleanliness, the prohibition of damaging and polluting nature, and spiritual values in treating nature as a mandate from Allah SWT. In addition, this article also highlights the importance of implementing the teachings of the hadith on cleanliness in the context of modern life, as a solution to various environmental problem faced by humanity today. With a qualitative approach and study of hadith texts, this article emphasizes that maintaining a clean environment is an integral part of Islamic ethics that must continoue to be lived out in the daily practices of the people.